OPTIMALISASI MINAT BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING - Riska Meyanti; Yohanes Bahari; Izhar Salim (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
The quality and the success of learning is strongly influenced by the ability and the accuracy of the teacher in choosing and using the learning models, there are various methods that can be used by teachers to deliver the subject matter, among others, problem solving learning model. Problem solving learning model is learning model that emphasize a logical problem. This learning model encourages students to think systematically by confronting problems related to the life in the community. This problem solving learning model is more appropriate to be used in sociology subjects, by solving social problems that exist in society. By seeing the low interest in learning, the students tend to be passive and just fixated on the book. These make the students have a low learning interest. Because the learning model used by the teacher influence the quality of the teaching process. By this learning model the teacher can improve students' learning interest in the learning process.